BKW EOS: history of modifications and further improvement of accuracy with temperature-dependent covolumes of polar molecules - Suceska, Muhamad (2022)
A hundred years ago (in 1921) Becker proposed an equation of state in which the repulsive term in van der Waals equation of state was replaced by an exponential function. Twenty years later, Kistiakowsky and Wilson modified Becker's equation and used it to calculate the detonation properties of nitroglycerine and mercury fulminate. The resulting equation of state, commonly called the BKW equation of state, is attributed to Becker, Kistiakowsky, and Wilson. Although it was not founded on a strict theoretical background, the BKW equation of state has been widely adopted in thermochemical codes to predict the detonation properties of explosives. Throughout the years, the accuracy of BKW has been significantly improved through proper calibration of the BKW constants and covolumes. This paper presents the concept of temperature-dependent covolumes of polar molecules (H2O and NH3) as a way to improve the accuracy of prediction of detonation properties of explosives, especially those explosives producing larger amounts of H2O and NH3. It was demonstrated that temperature-dependent covolumes describe more accurately experimental shock Hugoniots of polar molecules than constant covolumes, and the accuracy of prediction of detonation properties of HNO types of explosives is greatly improved.